2021
DOI: 10.46542/pe.2021.212.296304
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing solubility and antibacterial activity using multi-component crystals of trimethoprim and malic acid

Abstract: Aim: To improve the solubility and antibacterial activity of trimethoprim (TMP) by preparing its multicomponent crystals with malic acid (MA). Methods: Multicomponent crystals of TMP-MA were prepared by solvent co-evaporation. The solid-state properties were characterised by powder X-ray diffraction (PXRD), differential thermal analysis (DTA), Fourier transform infrared (FT-IR) spectroscopy, and scanning electron microscopy (SEM) analyses. The solubility was investigated in an aqueous medium, while the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…In the spectrum of multicomponent crystals of trimethoprim and mandelic acid, there was a shift in the wave number of the N-H group from pure trimethoprim 3467 cm -1 to 3345 cm -1 , a shift in the O-H wave number from 3388 cm -1 to 3155 cm -1 , this indicated the possibility of hydrogen bonding. The formation of multicomponent crystals of trimethoprim with malic acid conducted by Yuliandra et al, hydrogen bond formation occurs through N-H … O between the protonated pyrimidine cation in trimethoprim and the carboxylic anion of malic acid [14]. Similar interactions are also predicted in the formation of multicomponent crystals of trimethoprim and mandelic acid in this study.…”
Section: Fourier Transform Infrared (Ftir) Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…In the spectrum of multicomponent crystals of trimethoprim and mandelic acid, there was a shift in the wave number of the N-H group from pure trimethoprim 3467 cm -1 to 3345 cm -1 , a shift in the O-H wave number from 3388 cm -1 to 3155 cm -1 , this indicated the possibility of hydrogen bonding. The formation of multicomponent crystals of trimethoprim with malic acid conducted by Yuliandra et al, hydrogen bond formation occurs through N-H … O between the protonated pyrimidine cation in trimethoprim and the carboxylic anion of malic acid [14]. Similar interactions are also predicted in the formation of multicomponent crystals of trimethoprim and mandelic acid in this study.…”
Section: Fourier Transform Infrared (Ftir) Analysissupporting
confidence: 86%
“…Increasing drug solubility with the formation of multicomponent crystals has been widely carried out and has proven successful. One of them was the study of the formation of multicomponent crystals of trimethoprim and malic acid, which showed that trimethoprim was 2.5 times more soluble [14].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the MCC of trimethoprim-mandelic acid showed a shift in the wave number that occurred in the NH group from 3468.01 to 3350 cm -1 . A similar case also happened in the formation of MCC of trimethoprim-malic acid, which indicated a stretch in the NH group [22].…”
Section: Fourier-transform Infrared (Ft-ir) Spectroscopic Analysismentioning
confidence: 58%
“…Amongst several methods that have been introduced, one method generally generates better physical and chemical properties compared to their intact active ingredients, known as the formation of multicomponent crystals [9]. Previous studies related to the formation of multicomponent crystals of trimethoprim have been investigated, including the formation of trimethoprim-sulfamethoxazole [10], trimethoprim-citric acid [11], and trimethoprim-maleic acid [12]. Our previous study also showed an improvement in trimethoprim solubility using mandelic acid as the co-former by solvent drop grinding method, which increased about 2.73 times [13].…”
Section: Introductionmentioning
confidence: 99%
“…If ∆pKa of API and coformer ≥ 3, it will likely form a salt, while if ∆pKa <3, it will have the potential to develop a cocrystal. ACF (pKa = 4.7) and LGLN (pKa1=2.17 and pKa2=9.13) have ∆pKa 2.53 and 4.43 [17]. Synthon engineering can also predict the formation of cocrystals; LGLN has carboxyl and amide groups, while ACF has carboxyl and hydroxyl groups acting as donors or receptors to form hydrogen bonds [18,19].…”
Section: Introductionmentioning
confidence: 99%